P32 Role of non acid and proximal reflux in scleroderma-associated interstitial lung disease. (12th November 2015) - De Lauretis, A; Ward, S; Murray, C; Clayman, C; Ong, V; Denton, C; Bikov, A; Visca, D; Lindahl, G; Chetta, A; Aiello, M; Wuyts, W; et al.
Abstract : Background: Oesophageal involvement is extremely common in patients with scleroderma. This prospective observational study (NCT02136394 ) addresses the relationship between gastro-oesophageal reflux (GORD) and scleroderma-associated interstitial lung disease (SSc-ILD), and evaluates the clinical utility of noninvasive tests of microaspiration. Materials and methods: We present preliminary results of the first 27 enrolled patients (median age 59 [min/max 35/79], median FVC = 74% [38/128%], median DLCO = 39% [21/72%], female 70%, diffuse SSc 33%). Collected clinical data included 24 hr impedance (carried out off PPI), respiratory (K-BILD and Leicester cough questionnaires) and GORD symptom questionnaires (UCLA SCTC GIT 2.0 Questionnaire, Reflux Disease Questionnaire RDQ), as well as full lung function test data. Pepsin levels were measured in saliva in all patients, and in a subset of 6 patients in bronchoalveolar lavage (BAL). Results: Non acid reflux and proximal reflux were detected in 54% and 49% of patients, respectively. In the subgroup of patients with normal DeMeester score (i.e. global impedance index of acid exposure), 66% had non acid reflux episodes. The DeMeester score (median 14.2 [min/max 0.8/156]) was correlated with total scores GORD questionnaire scores (e.g. RDQ, r = 0.68 p = 0.003; GIT 2.0, r = 0.68 p = 0.004), but not with K-BILD, Leicester questionnaire, or saliva pepsin. Proximal reflux episodes were moderately correlated with the Leicester total score (r = -0.76 p = 0.002) and with saliva pepsin (r = 0.46 p = 0.05). Saliva pepsin (median concentration 2.34 ng/ml [2.34/12.4]) was correlated with the impedance cough index association (r = 0.53, p = 0.02). BAL pepsin was present in all six cases (median concentration 2.34 ng/ml [2.34/12.4]) and was correlated with FVC (r = -0.8, p = 0.04). Lung function test parameters were not correlated with saliva pepsin, but were significantly, if loosely, correlated with impedance measures of acid exposure in the recumbent position (e.g.% time of exposure, r = -0.43 p = 0.04). Conclusions: Proximal and non acid reflux are highly prevalent in the SSc-ILD population and are associated with a high symptom burden. Pepsin is measurable in BAL of SSc-ILD patients and suggests microaspiration into the lungs, although larger numbers are needed to confirm these findings and define whether saliva pepsin measurement could represent a useful non invasive marker of microaspiration.